Internalisasi Nilai Religius Sebagai Strategi Pembentukan Karakter Dalam Menghadapi Dekadensi Moral: Analisis Budaya Madrasah Semi Pesantren di MA Al Islamiyah - Ramadinia Allsyafira; Amin Fauzi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze the process of internalizing religious values through the semi-pesantren madrasah culture at MA Al Islamiyah as a response to the phenomenon of moral decadence among the younger generation in the era of globalization and digitalization. The study uses a descriptive qualitative approach with primary data sources in the form of the head of the madrasah, Islamic Education teachers, and students, as well as secondary data in the form of program documents and madrasah rules and regulations. Data were collected through observation, in-depth interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing with triangulation validity testing of sources and methods. The results show that the semi-pesantren madrasah culture at MA Al Islamiyah is implemented through structured religious programs such as congregational prayers, tahfidz, muhadharah, and the BENYAMIN S (Clean, Comfortable, Beautiful, and Polite) program, which is oriented towards the formation of social ethics. The internalization process takes place through habituation, teacher role modeling, and persuasive guidance so that religious values are not only understood cognitively but also internalized and practiced in daily life. The impact is seen in increased religious discipline, respect for teachers, and students' social responsibility. This study confirms that the semi-pesantren madrasah culture functions as an effective hidden curriculum in building religious character and akhlakul karimah (good character) and serves as a preventive strategy against moral crises in the digital age.